Increase of purification capacity and the performance of slow filtering in the removal of bacteria in an activated carbon-soil-sand filter unit - Rahman, Md. Mokhlesur; Mohd Yusof, Alias; Wan Nik, Wan Sani (Centre for Promoting Ideas, USA, 2011)
Abstract Mini scale carbon-soil-sand filtering system can be highly effective on surface waters, without requiring the use of coagulation preceding filtration. It is effective in removing suspended solids, toxic metals and imposes a 98-99 % reduction in bacteria. A novel filtering system is described here, where the bacterial removal zone was set above the purification zone in the filtering system. This paper gave an introduction on the working principle of this novel filtering system, which was developed for a single-family size in rural community. It demonstrated the visualization of the flow field and the exchange of water between the different layers. It also clarified the mechanism for bacteria removal in an activated carbon-soil-aquifer filtering system. This phenomenon can be explained by the formation of bacterial flocks where bacteria were removed by irreversible separation and adsorption. The bacteria were also removed from the liquid phase by separation onto the ceramic filter. Carbon-soil-aquifer filtering systems operating at a temperature of 250 C to 300 C were fed with source waters characteristic of polluted surface water samples. Coliform and total count (TC) data are presented. Slow filtration lengthens filter runs and produces filtered water with less taste and odour, and free of enteric bacteria. As the quantity and quality of the world's traditional drinking water sources decline, the use of alternative water sources grows.